Transcriptome analysis unraveled potential mechanisms of resistance to Haemonchus contortus infection in Merino sheep populations bred for parasite resistance - Runfeng Zhang; Fang Liu; Peter Hunt; Congjun Li; Lichun Zhang; Aaron Ingham; Robert W. Li (Veterinary Research, 2019)
Abstract Haemonchus contortus is one of the most pathogenic gastrointestinal nematodes in small ruminants. To understand molecular mechanisms underlying host resistance to this parasite, we used RNA-sequencing technology to compare the transcriptomic response of the abomasal tissue, the site of the host-parasite interaction, of Merino sheep bred to be either genetically resistant or susceptible to H. contortus infection. Two different selection flocks, the Haemonchus selection flock (HSF) and the Trichostrongylus selection flock (TSF), and each contains a resistant and susceptible line, were studied. The TSF flock was seemingly more responsive to both primary and repeated infections than HSF. A total of 127 and 726 genes displayed a significant difference in abundance between resistant and susceptible animals in response to a primary infection in HSF and TSF, respectively. Among them, 38 genes were significantly affected by infection in both flocks. Gene ontology (GO) enrichment of the differentially expressed genes identified in this study predicted the likely involvement of extracellular exosomes in the immune response to H. contortus infection. While the resistant lines in HSF and TSF relied on different mechanisms for the development of host resistance, adhesion and diapedesis of both agranulocytes and granulocytes, coagulation and complement cascades, and multiple pathways related to tissue repair likely played critical roles in the process. Our results offered a quantitative snapshot of changes in the host transcriptome induced by H. contortus infection and provided novel insights into molecular mechanisms of host resistance.